Hubungan Penggunaan Cahaya Lampu Saat Tidur Dengan Kualitas Tidur Pada Siswa Siswi Kelas XI Jurusan IPS Di SMAN 25 Kab. Tangerang - Deslaranti; Siti Rochmani; Lastri Mei Winarni (Jurnal Kesehatan, 2022)
Background: In its development stage, adolescents are faced with health problems including poor sleep quality. Data in Indonesia, most of the sleep quality of adolescents is not fulfilled. Teenagers generally need 8-9 hours of sleep every day. Lack of sleep quality will have an impact on decreased activity and concentration in learning and sleep disturbances. One of the factors for the lack of quality sleep is caused by the use of light. Light during sleep can affect the performance of sleep hormones. The habit of sleeping in a dark or light room will have an impact on the quality of one's sleep. The purpose: To determine the relationship between the use of light while sleeping with sleep quality in class XI students in the Social Sciences Department at SMAN 25 Kab. Tangerang. Methods: Quantitative research with a cross sectional approach, a population of 142 students of class XI Social Studies Department at SMAN 25 Kab. Tangerang, the sample in this study was 104 respondents using simple random sampling technique. The data instrument is a questionnaire with data analysis, namely the Chi square test. Results: The results showed a significance value of 0.001 (p <0.005) which stated that there was a relationship between the use of lamps during sleep and sleep quality in students. Conclusion: Nurses can provide education both directly to adolescents and parents who play an important role in monitoring child development. The results of this study can be used as an illustration for nurses to provide counseling or health education in an effort to maximize the quality of adolescent sleep.